(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
In the spiritual form in Yesenin’s poetry, the features of the people were clearly revealed - its "restless, daring strength", scope, cordiality, spiritual restlessness, deep humanity. Yesenin’s whole life is closely connected with people. Maybe that is why the main characters of all his poems are ordinary people, in every line one can feel close, not weakening over the years, connection between the poet and the person - Yesenin with Russian peasants